GAMBARAN PENGETAHUAN PERAWAT PELAKSANA DALAM PENANGANAN PASIEN GAWAT DARURAT DI RUANGAN IGDM BLU RSUP. Prof. Dr. R. D KANDOU MANADO - Joice Mermy Laoh; Konny Rako (Jurnal Ilmiah Perawat Manado (Juiperdo), 2014)
Services / emergency care includes nursing services aimed suddenly be in distress or likely to become critical and threatened his life or / limbs (will become disabled) when not get help quickly and precisely. The results observed in 61.2% of nurses Prof Dr IGDM BLU. Dr R. D Kandou Manado not perform emergency patient handling in accordance with standard procedures, in which sometimes the patient has been in the ER room more than 8 hours, the primary assessment conducted after nursing actions performed and also when nurses perform cardiopulmonary resuscitation, compressing the depth and position of nurses who do not comply with existing procedures and do not use the board when compressing resuscitation, airway exemption is not done (head tilt, chin lift, jaw thrust) and collaborative drug delivery is sometimes too late. The research objective of this scientific paper is to determine the knowledge of nurses in the management of emergency patients in the hospital room IGDM BLU Prof. Dr R.D. Kandou Manado. The benefits of this research is a scientific paper can be used as input for nursing personnel in the room IGDM BLU Dr Prof. Dr. RD Kandou Manado in handling emergency patients for improved patient care emergency. This research is a descriptive study. Sampling techniques using total sampling amounted to 31 respondents, the research instruments using a questionnaire of 20 statements and to use it ananlisa Data P = f / nx 100. The results of the description of the knowledge nurses in the management of emergency patients in the hospital room IGDM BLU Prof. Dr. RD Kandou Manado shows that of the 31 respondents surveyed respondents obtained knowledge in handling emergency patients in enough categories that as many as 19 respondents (61.3%), well as much as 9 respondents (29%), and less by 3 respondents (9.7 %). Based on these studies it can be concluded that the level of knowledge of nurses in the management of emergency patients is quite. It is recommended to nurses who served in the room to further improve the education and knowledge in handling emergency patients